Exploring the relationship between government institutional support and export strategic performance - Takyi, Lydia Nyankom (Teorija in praksa, 2022)
The study presented in the article examined the mediating role played by internationalisation in both government financial support–export strategic performance and government non-financial support– export strategic performance relationships. The moderating role of a strategic alliance in the relationships between government financial support and degree of internationalisation, and between government nonfinancial support and degree of internationalisation, was also considered. The study entailed a cross-sectional survey and included 301 indigenous export firms in Ghana. The reliability and validity of the data was tested using confirmatory factor analysis, with structural equation modelling as the primary means of analysis, run using Amos (v.23). It was concluded that both government financial support and non-financial support had a direct positive influence on export strategic performance. These relationships were partially mediated by the degree of internationalisation. Strategic alliance positively moderated the relationships between government financial support and degree of internationalisation, and also between government non-financial support and degree of internationalisation
Keywords: export; finančna vladna podpora; government financial support; government non-financial support; internationalisation; Izvoz; izvozna strateška uspešnost; nefinančna vladna podpora; Poslovni uspeh; strategic alliance; strategic performance; strateško zavezništvo; Subvencije